2012
DOI: 10.2478/v10201-011-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yoga Exercise on Metabolic and Homeostatic Parameters of Insulin Resistance

Abstract: A b s t r a c tThe aim of this study is to assess the effect of yoga exercise on the anthropometric parameters and metabolic parameters in individuals regularly exercising yoga as well as to assess the possible impact on cardiovascular risk prevention. The study sample composed of two groups: A (57 healthy control) and B (61 subjects exercised yoga). For each group were measured: blood pressure, body mass index (BMI) and laboratory values of total cholesterol, triglycerides, high density lipoproteins (HDL) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In order to measure insulin resistance, HOMA-IR formula was employed. This formula is HOMA-IR = fasting insulin (µIU/mL) × fasting glucose (mmol/L)/22.5 [8,16].…”
Section: Discussionmentioning
confidence: 99%
“…In order to measure insulin resistance, HOMA-IR formula was employed. This formula is HOMA-IR = fasting insulin (µIU/mL) × fasting glucose (mmol/L)/22.5 [8,16].…”
Section: Discussionmentioning
confidence: 99%
“…6,10,42,43 Research on the effectiveness of yoga in improving insulin resistance was done by Sahay, 12 involving only 5 subjects, in which the measurement of insulin resistance was not performed directly by calculating HOMA-IR.Several other researches using yoga to improve insulin resistance have used HOMA-IR as an outcome and showed a decline in HOMA-IR although largely not statistically significant. [13][14][15] Correspondingly, Qigong relaxation exercises by Sun et al 16 performed in patients with T2DM also showed HOMA-IR improvement although still not significant, but improvement of fasting glucose and HbA1c can be achieved significantly. A study conducted by Nidhi et al 11 which involving 90 subjects with polycystic ovary syndrome, showed an improvement in insulin resistance (HOMA-IR) through the practice of yoga for 1 h per day for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…11 Another studies of physical and relaxation theraphy such as yoga and Qigong showed reduced stress level and might improves insulin resistance. [12][13][14][15][16][17][18][19][20] Our hypothesis is the reduced stress level will decrease plasma cortisol level through hypothalamuspituitary-adrenal (HPA) axis pathway and improve glycemic control and insulin resistance in diabetic patients. This study was conducted to investigate the effect of LPD on insulin resistance in T2DM without depression.…”
Section: Introductionmentioning
confidence: 99%